HUBUNGAN TINGKAT KEPATUHAN MINUM OBAT ANTIDIABETIK ORAL TERHADAP KADAR HEMOGLOBIN TERGLIKASI (HbA1c) PADA PASIEN DIABETES MELITUS TIPE 2 - Wirawan Adikusuma; Nurul Qiyaam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
Treatment adherence is needed to support the success of therapy in patients with type 2 diabetes mellitus (T2DM). The purpose of this study is to examine the relationship of adherence level of oral antidiabetic to HbA1c level of T2DM patient. This research was conducted by using crossectional method by taking prospective data during April - June 2017 period. The subjects of this study were 40 patients of outpatient T2DM in Internal disease polyclinic in West Nusa Tenggara Hospital, Indonesia. Data collecting was conducted by using the pill count method and HbA1c levels were taken based on laboratory test results. The results showed that adherence level of T2DM patients was classified as adherence 50% and non-adherent 50%. There was a negative correlation between T2DM patient treatment adherence to HbA1c levels (r = 0.081, p = 0.619). Based on this it is shown that there is no relationship between the level of adherence to taking oral antidiabetic drug to HbA1c.